1989
DOI: 10.1111/j.1600-0609.1989.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum from patients with various thrombopoietic disorders alters terminal cytoplasmic maturation of human megakaryocytes in vitro

Abstract: Human bone marrow was depleted of progenitors (CFU‐MK), but enriched for recognizable megakaryocytes (MK), and placed in cultures with serum from either normal donors (NABS) or patients with primary (PTS) or secondary (STS) thrombocytosis, autoimmune thrombocytopenia (ATS) or aplastic anemia (AAS). Mean MK diameters shifted during the 3–4 days of incubation. Endomitotic figures were visible and mean ploidy increased slightly during cytoplasmic maturation, where decreases in immature cells (stages 1 and 2) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…To determine why the number of MK colonies was increased in ITP, we aimed to define the capacity of sera of ITP patients to enhance megakaryocytopoiesis. Such an effect has already been reported by other authors in thrombocytopenia with a decreased megakaryocytic mass (13,14). In this study we also notice such an effect in thrombocytopenia of peripheral origin where the megakaryocytic mass is increased; however, we note that its intensity remains rather moderate.…”
Section: Discussionsupporting
confidence: 88%
“…To determine why the number of MK colonies was increased in ITP, we aimed to define the capacity of sera of ITP patients to enhance megakaryocytopoiesis. Such an effect has already been reported by other authors in thrombocytopenia with a decreased megakaryocytic mass (13,14). In this study we also notice such an effect in thrombocytopenia of peripheral origin where the megakaryocytic mass is increased; however, we note that its intensity remains rather moderate.…”
Section: Discussionsupporting
confidence: 88%
“…Studies carried out on rodents indicated that AChE is secreted into the demarcation membranes and extracellular spaces of megakaryocytes just before they disintegrate to form platelets. [46] The level of AChE could therefore control megakaryocytopoiesis, perhaps in a way similar to its role in neurotransmission.…”
Section: Resultsmentioning
confidence: 99%